DIGITAL LIBRARIES IN EDUCATION: A BIBLIOMETRIC ANALYSIS ON THE WEB OF SCIENCE - Suhada, Hofur; Yuadi, Imam (UPT. Perpustakaan Universitas Muhammadiyah Ponorogo, 2024)
This study aims to identify trends and developments in scientific publications related to digital libraries in education. The VOSViewer bibliometric analysis and visualization method was applied using the Web of Science (WOS) database from 2013 to early 2024. The study reveals significant developments in research over the past few years. It details research productivity and identifies the keywords 'higher education' and 'systematic review' as frequently associated with the main keywords. United states of america is identified as the most influential country in publications, with author Khan A and the journal Humanidades Inovacao as the most contributors. The study's conclusion confirms that scientific publications on digital libraries in education are experiencing positive growth, in line with the development of information and communication technology (ICT).